Karen's school trip - Martin, Ann M., 1955-; Tang, Susan; Copyright Paperback Collection (Library of Congress) (New York : Scholastic, 1992)
Karen's class at school is planning a field trip to the zoo but when the flu hits Ms. Colman's class, it looks like the trip may be cancelled.
"A Little Apple paperback."
Keywords: Schools -- Fiction; Influenza -- Fiction; Zoos -- Fiction; Schools -- Fiction; Influenza -- Fiction; Zoos -- Fiction